Analysis of Factors Affecting Sales Volume in the Tech Industry: A Multiple Regression Approach - Bai Qishan (SHS Web of Conferences)
This paper examines the factors influencing sales volume among listed tech companies, focusing on key variables such as market demand, stock price, and advertising costs. Using a multiple linear regression model, the study analyzes data from major tech firms, including Microsoft, Apple, and Tesla. The results reveal that advertising costs have a significant effect on sales volume, underscoring the importance of marketing expenditures in driving revenue growth. However, stock price and product price show less statistical significance, indicating these factors may have a smaller impact on sales compared to advertising. The findings emphasize the need for tech companies to strategically allocate marketing resources to optimize sales outcomes. Additionally, the study suggests expanding the scope of future research by incorporating a broader range of variables to better understand sales dynamics in the tech sector. Future studies could explore factors like technological innovation, market saturation, and consumer behaviour to offer a more comprehensive view of sales performance.